Вплив комерційного радіомовлення на квебекську пісенну поезію - Де Сюрмон, Ж. (Народна творчість та етнологія, 2012)
Jean Nicolas De Surmont. Impact of Commercial Radiobroadcast on Quebec Song Composition. In this article, we juxtapose the development of radio with the original song composition (chanson signée), and show correlations between historical conditions and the function of radio. The study focuses mainly on the socio-historical dimension of the chanson québécoise (our analyses could not include all artisans in the music industry such as tour managers, agents, producers, etc.).